Empowering Teachers: “Merdeka Belajar” Implementation Insights from Education Conference – A Qualitative Study - Dikdik Firman Sidik (Indonesian Journal of Education and Social Studies, 2022)
This study aims to evaluate the effectiveness of the Darul Hikam Education Conference (DHEC) in 2022 in improving teacher readiness in implementing the Merdeka Belajar Curriculum in junior high schools in Bandung City. The research method used is qualitative with a case study approach. Data was collected through interviews with 5 teachers who attended the conference and documentation of conference activities. Data analysis was carried out using qualitative analysis methods. The study found that the DHEC was effective in improving teacher readiness in implementing the Merdeka Belajar Curriculum. The conference provided teachers with important knowledge and skills related to the curriculum and helped them to develop a positive attitude towards the curriculum. Teachers perceived the conference as an important and effective learning opportunity that helped them to overcome various challenges in implementing the curriculum. The study also found that documentation of conference activities provided important insights into the effectiveness of the conference. These data sources provided evidence of the ways in which the conference helped to improve teacher readiness and facilitate the implementation of the curriculum. Overall, this study provides important insights into the effectiveness of the DHEC in improving teacher readiness in implementing the Merdeka Belajar Curriculum. The findings of this study have important implications for educational practitioners and policymakers who seek to improve the implementation of the curriculum in schools.